Assessment of the color of orange juice in the context of dietitians’ food preferences - Kardas, Marek; Kiciak, Agata; Szynal, Kamila; Sitkiewicz, Barbara; Staśkiewicz-Bartecka, Wiktoria; Bielaszka, Agnieszka (Frontiers in Nutrition, 2024)
Color is an integral part of product selection and is used to assess its attractiveness and quality. Dietitians are a group that influences the dietary choices of the population through education and promotion of rational eating behavior. The purpose of this study was to evaluate the color of selected juices in the context of dietitians' food preferences. In the first stage of the research, the color of orange juices was measured using a spectrophotometer. In the second stage, a sensory analysis was carried out using the ranking method. Participants were asked to assess the attractiveness of the color of juices through glasses and bottles without the original label and with the label. The juice with the best color turned out to be the juice which, according to L*a*b* parameters, was relatively dark and had an intense orange tint. As the juice with the worst color, they chose the juice that was colored green and blue. When assessing the color without and with the original label, the respondents indicated which one was significantly brighter and more yellow compared to the others. Dietitians prefer bright juices with a vibrant orange hue. Product packaging influences dieticians' choices regardless of the content. Instrumental control of color during product production and selection of packaging elements for attractive synergy are determinants of perceived attractiveness of juices in the study group.